Ovrecoming or suppressing ecofeminism? - Selak, Marija (Array, 2011)
Since problems of ecofeminism are orientated not only towards contemporary times, but also towards future, this paper will examine the role of technique in an attempt of their resolving. Post-modern, lets call it fluid, understanding of the Being as plurality is given as an alternative to often criticized horizon of classical metaphysic (reduced on monistic or factual understanding of Being in a sense of something that is given, firm and/or unchangeable). Precisely that post-modern understanding is often appreciated as a solution of ecological and feminist issues. Does a unity of a man and the machine, the same unity which bare attempt has produced ecological and other problems that we are affronting, truly offer their solution or do the old conditions of domination over women and domination over nature transfer in the idea of transhuman beings? Is the world of information as the essence of a cultural (human) world a solution of a „problem‟ of natural or is it a path to a new, repetitive, slavery? As an effort of answering this and other questions, reasoning of the idea of transhumanism (Bostrom – Sloterdijk) in a feminist discourse (Haraway) will be related to epistemological understanding of technique (Heidegger, Gehlen). This appreciation will be comprehended as the finalization of a dominant „stiff‟ metaphysical understanding of nature (as something that can be realized).